Pengaruh Kombinasi Emulgator CMC dan Tween 80 Terhadap Stabilitas Fisik Emulsi Minyak Ikan - Adiningsih, Retnowati (Jurnal Farmasi (Journal of Pharmacy), 2014)
Cod-liver oil emulsion in standard formula using gum arabic as emulsifying agent is considered to be “true” emulsifier. The disadvantage of gum arabic is it cannot be stored in along time because the emulsifier effect will vanish, so it has to be combined with other emulsifying agent such as CMC and Tween 80. The aim of the experiment was to study the influence of CMC and Tween 80 emulsifiers combination on physical stability of cod liver oil emulsion and the optimal concentration of CMC and Tween 80 emulsifiers to prepare a stable cod liver oil emulsion, indicated by there was no significant damage of the emulsion during the experiment. The experiment used 4 formulas which contain emulsifiers combinations: 0,25% CMC; 0,25% CMC : 10% Tween 80; 0,25% CMC : 20% Tween 80; 20% Tween 80. The observation of emultion stability includes emulsion type, separation percentage at room temperature, at 40° - 50°C temperature, at 3000 rpm centrifugally, viscosity and particle size determination. The result of the experiment indicated there was various stability of cod liver oil emulsion in each emulsifier combination. The statistic result indicated that CMC 0,25% had significant influence on separation percentage at room temperature, at 40° - 50°C, 3000 rpm centrifugally, viscosity and particle size of cod liver oil. Emulsion with emulsifiers combination of 0,25% CMC : 20% Tween 80 was the most stable emulsion because at the separation percentage examination, the viscosity and particle size had the best physical stability compared with other formula.